(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study assessed the knowledge and practices associated with use of various drugs for the purpose of prevention and treatment of Covid-19, during the rapid rise period of the COVID-19 outbreak. A self-developed questionnaire was distributed online/offline to 397 participants via the authors' networks and through popular social media Platforms, later on collected and statistically analyzed. On analysis we found that most of the participants have moderate to good knowledge of COVID-19. Our study shows that drugs for prevention of Covid-19 were used significantly more by females as compared to males (p-value < 0.05). Healthcare worker’s (HCW) use of drugs was quite high as compared to non-healthcare workers (NHCW) for prevention as well as for treatment of Covid-19 (p-value was significant < 0.05). ultivitamins, for prevention as well as treatment point of view (72.1% and 47.7% respectively). Next line of group used for preventive purpose was Antimalarials (Hydroxychloroquine/Chloroquine) used by 47.4% and then Ivermectin by 22.1% participants. Whereas from treatment point of view Antibiotics like Azithromycin and Doxycycline were next in line (used by 34.3% & 20.8% respectively).